2004
DOI: 10.1159/000079205
|View full text |Cite
|
Sign up to set email alerts
|

Altered Vascular Remodeling in Osteopontin-Deficient Atherosclerotic Mice

Abstract: Background: Osteopontin (OPN) is a cell-binding phosphoprotein with proposed functions in atherosclerosis. The aim of this study was to examine how OPN deficiency affects the atherosclerotic process. Methods: ApoE/LDL receptor/OPN triple knockout (ALO) mice were generated by crossing OPN null mice with ApoE/LDL receptor-deficient (AL) mice. Analysis were made on tissue sections from the aortic arch of 8-, 20- and 34-week female AL and ALO mice and included morphometric measurements, collagen staining, TUNEL st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 61 publications
2
10
0
2
Order By: Relevance
“…The expression of OPN has to our knowledge not previously been correlated with 18 F-FDG uptake. The high degree of correlation we found is supported by studies of knockout mice suggesting OPN as an important player in inflammation and atherogenesis [31], [32]. Both CD68 and OPN had independent predictive value for 18 F-FDG uptake in the multivariate linear regression analysis.…”
Section: Discussionsupporting
confidence: 73%
“…The expression of OPN has to our knowledge not previously been correlated with 18 F-FDG uptake. The high degree of correlation we found is supported by studies of knockout mice suggesting OPN as an important player in inflammation and atherogenesis [31], [32]. Both CD68 and OPN had independent predictive value for 18 F-FDG uptake in the multivariate linear regression analysis.…”
Section: Discussionsupporting
confidence: 73%
“…Matsui et al described 30–40% smaller atherosclerotic lesion areas in 36‐week‐old female Opn‐deficient atherosclerotic ( Opn/ApoE null) mice compared with ApoE null mice, due to less macrophages and lymphocytes in the lesion [37]. Also, in female 34‐week‐old Opn/ ApoE/ LDL receptor triple knockout mice, atherosclerotic lesion area is reduced compared with ApoE/ LDL receptor deficient mice [38]. Furthermore, it has been shown that transgenic mice that overexpress Opn are more prone to develop fatty streaks than wild‐type mice [39].…”
Section: Discussionmentioning
confidence: 99%
“…Osteopontin transgenic mice fed a high-cholesterol diet develop atherosclerotic lesions [59,60], whereas osteopontin deficiency reduces atherosclerosis in apoE–/– [61] and apoE/LDL receptor-deficient mice [62]. In vitro overexpression of osteopontin promotes vascular SMC proliferation [63], and in vivo overexpression is associated with increased thickening of the media with aging and of the intima after arterial injury [64].…”
Section: Discussionmentioning
confidence: 99%